2019
DOI: 10.2196/13617
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dropouts From an Electronic Health Platform for Lifestyle Interventions: Analysis of Methods and Predictors

Abstract: BackgroundThe increasing prevalence and economic impact of chronic diseases challenge health care systems globally. Digital solutions can potentially improve efficiency and quality of care, but these initiatives struggle with nonusage attrition. Machine learning methods have been proven to predict dropouts in other settings but lack implementation in health care.ObjectiveThis study aimed to gain insight into the causes of attrition for patients in an electronic health (eHealth) intervention for chronic lifesty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 19 publications
1
63
0
Order By: Relevance
“…In any digital health program, compliance is a key challenge and an essential factor for a successful outcome, as low compliance can threaten the validity of a study [ 18 ]. A substantial number of patients stop using apps before the completion of a program [ 19 ]. Several studies from different fields reported that compliance declined through the course of their study [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In any digital health program, compliance is a key challenge and an essential factor for a successful outcome, as low compliance can threaten the validity of a study [ 18 ]. A substantial number of patients stop using apps before the completion of a program [ 19 ]. Several studies from different fields reported that compliance declined through the course of their study [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the results indicated that RF has the highest average AUC in the process of 10-fold cross-validation, and RF use in the testing set showed performance consistent with that in the training/validation set. Many previous studies also found that RF performs better than many standard supervised learning techniques [54][55][56][57]. The main advantages of RF are as follows:…”
Section: Principal Findingsmentioning
confidence: 99%
“…Continued research that helps to identify those at baseline and throughout treatment who are most likely to eventually drop out of DHMI is critical to address central questions about who needs clinician support, when it should offered, and in what form it should be delivered. Recent research suggests that women and older users are particularly vulnerable to dropout when using digital lifestyle interventions and that dropout risk is highest in early sessions (Pedersen et al, 2019). Finally, further work is needed to improve DMHIs to address issues of patient safety given that clinical deterioration and suicide risk are substantial concerns among individuals with depression.…”
Section: Summary and Need For Future Research And Developmentmentioning
confidence: 99%